Pemanfaatan Dan Pengolahan Sampah Sebagai Upaya Dalam Menjaga Lingkungan Di Desa Senaru, Kecamatan Bayan, Kabupaten Lombok Utara - Baiq Sopiatul Apriani; Nadiani Wibawanindah; Diska Nila Cahyani; Khusnul Khotimah; Baiq Rerin Karlina; Lalu Muhammad Andrian; Lalu Arli Agus Setiawan; Indri Andriani Astuti; Amalia Mursyedani Fitri; Andi Chairil Ichsan (Universitas Mataram, 2022)
Senaru Village is one of the villages that has the potential to be developed both in terms of tourism, nature and the environment. This village is located in Bayan District, North Lombok Regency. Senaru village is a tourism village that is visited by many local and foreign tourists. In this village there is plastic waste that has not received further treatment. Plastic waste is a type of inorganic waste that takes 1000 years to completely decompose by the soil. In addition, Senaru Village is also one of the areas that has a lot of cashew fruit, but the utilization of cashew fruit by the surrounding community is still quite limited, namely the processing is still focused on the seeds while the meat has not been used optimally and some even throw it away as waste. Therefore, with this article, the author aims to invite the public to use and process plastic waste into ecobricks that have aesthetic value and utilize and process cashew meat into shreds that have a selling value to help the community's economy.